A stonemason with accelerated silicosis in the setting of tumour necrosis factor alpha inhibitor therapy. Issue 5 (4th July 2016) - Baird, Timothy; Putt, Michael; Dettrick, Andrew
Abstract : We present the case of a 26‐year‐old stonemason with accelerated silicosis in the setting of treatment for psoriasis with the tumour necrosis factor alpha (TNF‐alpha) inhibitor adalimumab. Accelerated silicosis is an important occupational lung disease with a poor prognosis and limited treatment options [1]. Although the exact pathogenesis remains unknown, it is suggested that secretion of cytokines, including TNF‐alpha, plays a central role in disease progression [1, 2]. Importantly, however, TNF‐alpha inhibitors, in addition to resulting in an increased risk of infection, are also now being seen to cause interstitial lung disease [3, 4]. To our knowledge, this is the first documented patient to develop silicosis whilst on TNF‐alpha inhibitor therapy. This case challenges the theory behind TNF‐alpha's exact role in the pathogenesis of silicosis and lung fibrosis, highlights the importance of monitoring individuals with both occupational and drug exposures, and illustrates the increasing difficulties physicians face in investigating patients with pulmonary infiltrates and multiple possible aetiologies. Abstract : This case report presents an interesting case of a young male stone‐mason who developed accelerated silicosis in the setting of TNF‐alpha inhibitor therapy for his psoriasis. The case challenges the complex immunological process behind the pathogenesis of silicosis, demonstrates the importance of appropriate monitoring of occupational and drug exposures, and illustrates the difficulties physicians face in diagnosing patients with pulmonary infiltrates and multiple possible aetiologies.